Trust me! I am a European Central Banker - Dirk Bursian; Sven Fürth (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
In the aftermath of the financial crisis, the ECB has experienced an unprecedented deterioration in the level of trust. This raises the question as to what factors determine trust in central banking. We use a unique cross-country dataset which includes a rich set of socio-economic characteristics and supplement it with variables meant to reflect a country's macroeconomic condition. We find that besides individual socio-economic characteristics, macroeconomic conditions play a crucial role in the trust-building process. Our results suggest that agents are boundedly rational in the trust-building process and that current ECB market operations may even be beneficial for trust in the ECB in the long-run.
urn:nbn:de:hebis:30:3-317873
Keywords: D1; E5; G21; H6; 330; Central Banking; European Central Bank; Financial Crisis; Fiscal Crisis; Trust